Une histoire sociale de la prostitution: Montréal, 1800-1850 - Poutanen, Mary Anne (Les éditions du remue-ménage, 2021)
La reconnaissance du travail ménager occupe les féministes depuis des décennies. Mais qu’ont à dire celles qui en ont fait leur gagne-pain, les travailleuses de l’ombre par excellence? Dans ce livre, Catherine Charron examine le travail domestique rémunéré au Québec entre les années 1950 et 2000. Elle expose les parcours d’une trentaine de femmes de la région de Québec et leur donne la parole. Dans un contexte où le marché du travail subit de profondes transformations, les boulots domestiques, loin de disparaître, se reconfigurent et continuent d’occuper une part non négligeable de la main-d’œuvre féminine. Tandis qu’une proportion croissante de femmes ont un meilleur accès à la scolarisation et au salariat, de nombreuses autres se trouvent refoulées dans diverses filières d’emplois domestiques: la garde d’enfants, l’aide à domicile pour les personnes âgées, les travaux d’entretien ménager. Les trajectoires des femmes interrogées par Catherine Charron, nées entre 1914 et 1958, illustrent le rapport changeant des femmes à l’emploi et à la famille à partir des années d’après-guerre ainsi que leurs réalités hétérogènes. À l’intersection du public et du privé, le travail domestique rémunéré s’exerce dans la continuité du travail gratuit assigné aux femmes au sein de la famille et de la communauté, ce qui contribue à le rendre invisible. Aux marges de l’emploi révèle cette face cachée de l’économie marchande et domestique, incontournable dans toute réflexion sur le travail, et rend justice à celles qui l’incarnent.
Keywords: 1800-1899; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; droits des femmes*; his4550; histoire; justice sociale; montréal; patriarcat; premier cycle; prostitution; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Whispers of the Unspeakable: New York and Montreal Newspaper Coverage of the Oscar Wilde Trials in 1895 - Robinson, Greg (Journal of Transnational American Studies, 2015)
Greg Robinson’s article “Whispers of the Unspeakable: New York and Montreal Newspaper Coverage of the Oscar Wilde Trials in 1895,” originally published in 2010 in the French-language journal Rue des Beaux Arts, no. 24 (2010), is here republished and—with much gratitude—translated (for the original text, please see http://www.oscholars.com/RBA/twenty-four/24.7/Articles.htm). Robinson’s transnational study focuses on how reading the specific language of newspaper reports of the Oscar Wilde case, literally from a distance, from places less emotionally attached to and nationally distinct from the scandal’s epicenter in London, England, provides insight into “the state of everyday public knowledge and discussion of (homo)sexuality, at least west of the Atlantic”; thus Robinson’s fascinating research, which involves numerous newspapers—from the elite New York Times to the New York Herald, from the Montreal Daily Star to the French-language papers of Quebec—concludes that the popular press, read transnationally, offers key insights into the developing attitudes toward and levels of interest in the newly forming identity of the “homosexual” across societies.
Keywords: 1800-1899; amériques; analyse comparée; analyse de discours; approches et analyses; cours; discipline; discours dominant; discours médiatique; his4860; histoire; homophobie; hétérosexisme; montréal; new york; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; systèmes d'oppressions; thématiques

In the days of our grandmothers: a reader in Aboriginal women's history in Canada - Kelm, Mary-Ellen; Townsend, Lorna (University of Toronto Press, 2006)
From Ellen Gabriel to Tantoo Cardinal, many of the faces of Aboriginal people in the media today are women. In the Days of Our Grandmothers is a collection of essays detailing how Aboriginal women have found their voice in Canadian society over the past three centuries. Collected in one volume for the first time, these essays critically situate Aboriginal women in the fur trade, missions, labour and the economy, the law, sexuality, and the politics of representation. (Midwest).
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; commerce; commerce de peaux; cours; discipline; droit; droits des femmes*; droits des femmes* autochtones; famille; féminisme autochtone; histoire; histoire et politique; pol4105; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sexualité; thématiques; travail

Patience & Sarah - Miller, Isabel (Arsenal Pulp, Paperback, 2005)
Winner of the 1969 American Library Assoc. 's first Gay Book Award One of the "Best 100 Best Gay and Lesbian Novels of All Time" (Publishing Triangle) Set in the nineteenth century, Isabel Miller's classic lesbian novel traces the relationship between Patience White, an educated painter, and Sarah Dowling, a farmer, whose romantic bond does not sit well with the puritanical New England farming community in which they live. Ultimately, they are forced to make life-changing decisions that depend on their courage and their commitment to one another. First self-published in 1969 in an edition of 1,000 copies, it garnered increasing attention to the point of receiving the American Library Association's first Gay Book Award. Patience & Sarah is a historical romance that was a touchstone for the burgeoning gay and women's activism of the late 1960s and early 1970s; it celebrates the joys of an uninhibited love between two strong women with a confident defiance that remains relevant today. This edition features an appendix of supplementary materials, as well as an introduction by Emma Donoghue, whose numerous books include Stirfry, Hood, and Life Mask, which was shortlisted for a 2005 Lambda Literary Award and the Ferro-Grumley Award. Her 2010 novel Room was shortlisted for the Man Booker Prize and won the Rogers Writers Trust Fiction Prize. Little Sister's Classic edition now in its second printing!
Keywords: 1800-1899; amour; amériques; littérature; personnes lesbiennes; périodes historiques; ressource en ligne; roman; régions géographiques; sexualité; thématiques; états-unis

Gay New York : 1890-1940 - Chauncey, George (Histoire de la pensée, 2003)
Identifie la période de l'âge d'or de la tolérance et de la culture homosexuelle à New York entre 1890 et 1930 en explorant l'organisation spatiale et la structure sociale du monde des homosexuels. Mais la crise économique et sociale des années 1930 ainsi que des lois plus répressives allaient contraindre les homosexuels à devenir plus discrets et la culture gay à devenir clandestine.
Keywords: 1800-1899; 1900-1999; LGBTQIA2+; amériques; cours; discipline; his4860; histoire; histoire et politique; homosexualité; identités LGBTQIA2+; lesbiennes; new york; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; thématiques; états-unis

L'homosexualité masculine et les discours sur le sexe en contexte montréalais de la fin du XIXe siècle à la Révolution tranquille - Hurteau, Pierre (Histoire sociale / Social History, 1993)
La croyance populaire ainsi qu'une certaine théologie accordent souvent au discours religieux sur l'homosexualité une permanence doctrinale qu'il n'a pas. Les mythes populaires ont longtemps attribué la stigmatisation sociale de l'homosexualité au récit de Sodome. La critique historique du rapport entre religion et homosexualité permet cependant de mettre en évidence le caractère construit de ce discours et ses rapports avec le juridique et le médical. Le présent article veut établir de quelle manière ces discours ont pu s'élaborer au Québec, et particulièrement dans la région montréalaise, entre la fin du XIXe siècle et la Révolution tranquille. L'approche historique suggère une nouvelle herméneutique qui met en lumière les véritables impulsions qui sous-tendent le discours religieux sur l'homosexualité. Popular belief and certain types of theology often ascribe a continuity of doctrine to the religious discourse on homosexuality which, in fact, this discourse does not have. Popular myths have long attributed the social stigma of homosexuality to the story of Sodom. Historical criticism of the relationship between religion and homosexuality will bring to the fore the social construction of the religious discourse and its historical connections with the secular discourses of law and medicine. The following article will try to demonstrate how these discourses developed in Quebec, and particularly in the Montreal region, from the end of the nineteenth century to the Quiet Revolution. The historical approach taken here puts forward a new interpretation that brings to the light the real motivations that underlie the religious discourse on homosexuality.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; LGBTQIA2+; Québec (Province); amériques; approches et analyses; canada; cours; discipline; discours dominant; discours religieux; his4860; histoire; histoire et politique; homophobie; homosexualité; hétérosexisme; montréal; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; révolution tranquille; sciences humaines; sexualité; soc2014; sofia; systèmes d'oppressions; thématiques

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Théorie de la politique sexuelle - Millett, Kate (La politique du mâle, 1971)
Réédition d'un ouvrage paru chez le même éditeur en 1971. C'est une analyse critique d'une certaine envergure, souvent virulente et parfois contestée, de la prétendue supériorité du mâle. Trois parties bien distinctes : 1. La politique sexuelle. L'auteur dégage l'aspect politique souvent négligé de la sexualité. C'est le sujet de la thèse soutenue par l'auteur, à partir des concepts de puissance et de domination utilisés dans les relations entre les sexes - 2. L'arrière-plan historique. Fait ressortir les transformations de la relation entre les sexes : la révolution sexuelle entre 1830 et 1930; le climat de réaction entre 1930 et 1960 - 3. Le reflet littéraire. Etude basée sur la critique littéraire. L'auteur y montre comment quatre écrivains, Lawrence, Miller, Mailer et Genet, ont contribué à perpétuer l'idée de domination masculine. Importante bibliographie.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cours; fem1000; féminisme matérialiste; féminisme radical; patriarcat; premier cycle; périodes historiques; régions géographiques; sexualité; systèmes d'oppressions; thématiques; états-unis